Module on solution chemistry using understanding by design (UbD) framework - Ferrer, Ammie Penalba (Animo Repository, 2012)
This dissertation implemented and evaluated a module that was developed by the researcher using the backward design process or Understanding by Design (UbD) framework. This also investigated how it affects students conceptual understanding and how it varies with learning style and motivation. This was conducted among sixty four (64) 3rd high school students of Cavite State University Science High School for ten days of SY 2011-2012. The developed module, Module on Solution Chemistry, includes varied activities that were designed using the Process-Oriented Guided-Inquiry Learning (POGIL) approach. Qualitative and quantitative data were collected using the instruments: (1) Concept Test on Solution Chemistry (CTOS) developed by the researcher (2) on-line version of the Index of Learning Style questionnaire by Felder and Solomon (1997) (3) Motivated Strategies for Learning Questionnaire (MSLQ) developed by Pintrich, Smith, Garcia and Mc Keachie (1991) (4) Structured interview (5) Reflective journals (6) Module evaluation questionnaires (for content experts, UbD experts and students) and (7) observational checklist for the classroom observers. The CTOS was administered both as a pretest and a posttest to look into the students level of conceptual understanding before and after the module intervention. In addition, MSLQ and ILS questionnaires were also accomplished by the students to identify their learning styles and motivation for learning. Additionally, students were asked to accomplish journals to investigate further their conceptual understanding. Exit interviews were also done with six students to know more about students perceptions of the entire learning experience during the intervention. Students and invited classroom observers also rated the actual module intervention. The content experts, UbD experts, classroom observers and students all agreed that the module unit design was feasible and appropriate for teaching the topic Solutions. Furthermore, the study revealed that there was a significant difference from the pretest and posttest scores of the students as reflected in the T-value of -10.601, which is highly significant at 0.05 level of significance. It implies that module intervention could facilitate students learning and could allow them to understand the topic Solutions better. However, ANOVA revealed there were no significant differences between the mean scores achieved by the students with different learning styles and motivations, suggesting that the module does not favor any group of learners categorized according to their learning styles and motivations.